The impact of COVID-19 on the financial performance: a case study of the Lithuanian transport sector - Paulina Periokaitė; Nomeda Dobrovolskienė (Insights into Regional Development)
The changing global situation due to the outbreaks of COVID-19 is causing a crisis, not only in terms of healthcare but also in economic terms. Companies are faced with hasty decisions to avoid financial problems or even bankruptcy. Both in theory and practice, there are often more negative than positive effects of the coronavirus outbreak on transport sector business, but this topic has not yet been sufficiently explored due to the novelty of the situation and the divergent opinions of authors on some matters. The most significant impact is emphasised in the case of air transport, and the least studied area is road transport activity, which in Lithuania comprises the largest share of all modes of transport. It is observed that transport companies experience a decline in profitability indicators during the first wave of COVID-19. In the course of the investigation, the expert survey identified the most affected profitability and liquidity indicators of road transport companies. Relative financial indicators and a study of the financial results of coronavirus-related quarantine carried out using paired correlation analysis showed that there is an unequal connection between the number of days of quarantine in Lithuania and the relative financial indicators of road transport companies. Therefore, the crisis caused by COVID-19 is likely to have a positive or negative impact on the financial performance of a company, depending on the company’s activity. However, in some cases, there may be no impact at all. The monitoring of the constantly changing coronavirus crisis and the corresponding economic situation is an important immediate and continuous participation in the monitoring and control of the financial situation of companies.